Orthorexic eating behavior among dietitians and nutrition students in Brazil: A cross-sectional study of prevalence and agreement between ORTO-15 and DOS-BR (Research, Society and Development, 2025)
Previous research has reported substantial heterogeneity in prevalence estimates of orthorexic eating behavior. This study aimed to describe its prevalence in a specific academic context and to analyze associated factors. A cross-sectional online survey was conducted using two assessment tools (ORTO-15 and DOS-BR), along with sociodemographic, academic, anthropometric, clinical, and dietary intake data. The sample included 309 dietitians and 177 Nutrition college students from a large Brazilian university. According to the ORTO-15, 90.90% of participants were classified as presenting orthorexic eating behavior, whereas 10.90% were classified as at risk/present according to the DOS-BR, with no significant differences between dietitians and students. Agreement between the tools was poor (kappa = 0.024, p = 0.015), and Nutrition students had higher DOS-BR scores. Factors associated with orthorexic eating behavior (DOS-BR) included preoccupation with food additives and calorie content, history of eating disorders, increased concern with food after the Nutrition course reported by family and friends, weighing foods, and self-reported food allergies/intolerances. The findings highlight substantial differences between assessment tools, with the DOS-BR providing a more conservative and psychometrically robust evaluation in this academic context.